2007
DOI: 10.1523/jneurosci.0237-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Induced Neurogenesis in the Hippocampus of Adult Nonhuman Primates

Abstract: New neurons are generated in the adult hippocampus of many species including rodents, monkeys, and humans. Conditions associated with major depression, such as social stress, suppress hippocampal neurogenesis in rodents and primates. In contrast, all classes of antidepressants stimulate neuronal generation, and the behavioral effects of these medications are abolished when neurogenesis is blocked. These findings generated the hypothesis that induction of neurogenesis is a necessary component in the mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
274
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(289 citation statements)
references
References 83 publications
11
274
0
4
Order By: Relevance
“…Although adult NPCs hold substantial promise for neural repair after brain injury, their mobilization is hampered by the lack of knowledge about the molecular mechanisms controlling adult neurogenesis under normal and pathophysiological conditions. Pleiotropic signaling molecules [e.g., retinoic acid (RA), Wnt, and brain-derived growth factor (BDNF)] as well as antidepressant and anticonvulsant drugs (e.g., fluoxetin and sodium valproate) have been implicated in regulating adult NPC proliferation, differentiation, or survival in vivo (2)(3)(4)(5)(6)(7)(8). Therefore, it may be possible to develop neurogenic agents for pharmacological intervention specifically directed at the endogenous NPC pool.…”
mentioning
confidence: 99%
“…Although adult NPCs hold substantial promise for neural repair after brain injury, their mobilization is hampered by the lack of knowledge about the molecular mechanisms controlling adult neurogenesis under normal and pathophysiological conditions. Pleiotropic signaling molecules [e.g., retinoic acid (RA), Wnt, and brain-derived growth factor (BDNF)] as well as antidepressant and anticonvulsant drugs (e.g., fluoxetin and sodium valproate) have been implicated in regulating adult NPC proliferation, differentiation, or survival in vivo (2)(3)(4)(5)(6)(7)(8). Therefore, it may be possible to develop neurogenic agents for pharmacological intervention specifically directed at the endogenous NPC pool.…”
mentioning
confidence: 99%
“…Antidepressant-induced hippocampal neurogenesis occurs in bonnet monkeys (33) and antidepressant treatments in rodents appear to enhance emotion regulation by increasing neurogenesis in the ventral hippocampal dentate gyrus (1, 7). The neurogenic effect we observed in squirrel monkeys likewise tended to be greater in the anterior (ventral in rodents) compared with posterior (dorsal in rodents) hippocampal dentate gyrus, but this difference in our sample of six subjects in each housing condition was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have found that antidepressants dramatically enhance adult hippocampal neurogenesis in species ranging from rodents to nonhuman primates to humans ( Fig. 1) (Malberg et al 2000;Malberg and Duman 2003;Santarelli et al 2003;Encinas et al 2006;Perera et al 2007;Boldrini et al 2009;Pinnock et al 2009). For example, SSRI or tricyclic antidepressant (TCA)-treated patient groups with major depression had more NESTIN þ neural progenitor cells and Ki-67 þ dividing cells compared with untreated patients or control groups.…”
Section: Effects Of Antidepressant Treatment On Adult Neurogenesismentioning
confidence: 99%